2015
DOI: 10.1099/mic.0.000123
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the TonB1 and TonB2 proteins in haemin iron acquisition and virulence in Riemerella anatipestifer

Abstract: Two TonB systems in Riemerella anatipestifer were found and characterized as ExbB1-ExbD1-TonB1 and ExbB2-ExbD2-ExbD29-TonB2, but the significance of two sets of TonB complexes in R. anatipestifer is not clear. In this study, by deleting the tonB1 or tonB2 gene of R. anatipestifer strain CH3, we investigated the roles of the TonB1 and TonB2 proteins in iron acquisition and virulence. The results showed that strain CH3 could utilize haemin as the sole iron source in the presence of L-cysteine, but haemin iron ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Since it had been demonstrated that R. anatipestifer was able to obtain iron but not a heme source from G. mellonella larva infection, we wondered whether the G. mellonella larva model could be used to evaluate virulence genes related to heme uptake. As a proof of concept, we evaluated the virulence of the tonB1 mutant, tonB2 mutant, and tonB1 tonB2 mutant in the G. mellonella larva model since it has been shown that both tonB1 and tonB2 are involved in heme transport (36) and virulence (37) in ducklings. In the duckling model, consistent with a previous report (37), injection with 10 9 CFU of the tonB1 mutant, tonB2 mutant, and tonB1 tonB2 mutant resulted in no death within 7 days after injection (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it had been demonstrated that R. anatipestifer was able to obtain iron but not a heme source from G. mellonella larva infection, we wondered whether the G. mellonella larva model could be used to evaluate virulence genes related to heme uptake. As a proof of concept, we evaluated the virulence of the tonB1 mutant, tonB2 mutant, and tonB1 tonB2 mutant in the G. mellonella larva model since it has been shown that both tonB1 and tonB2 are involved in heme transport (36) and virulence (37) in ducklings. In the duckling model, consistent with a previous report (37), injection with 10 9 CFU of the tonB1 mutant, tonB2 mutant, and tonB1 tonB2 mutant resulted in no death within 7 days after injection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a proof of concept, we evaluated the virulence of the tonB1 mutant, tonB2 mutant, and tonB1 tonB2 mutant in the G. mellonella larva model since it has been shown that both tonB1 and tonB2 are involved in heme transport (36) and virulence (37) in ducklings. In the duckling model, consistent with a previous report (37), injection with 10 9 CFU of the tonB1 mutant, tonB2 mutant, and tonB1 tonB2 mutant resulted in no death within 7 days after injection (Fig. S4A); parallel injection with the wild-type strain resulted in a mortality rate of 78% for ducklings 7 days after injection (P Ͻ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…R.anatipestifer can infect various types of avian species, such as ducks, geese, turkeys, and some wild birds. R.anatipestifer infection is a contagious disease, that causes enormous economic losses to the poultry industry worldwide (8).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, OmpA [10]; TonB, which is involved in heme transportation [1113]; the TonB-dependent receptors B739_1208 and B739_1343 [14, 15]; the wza -like gene, which is involved in capsule biosynthesis [16]; and AS87_04050, M949_1556 and M949_RS01915, which are involved in lipopolysaccharide biosynthesis [1719] have been identified as potential virulence factors. In these studies, the functions of these genes were identified via gene deletion using an antibiotic cassette for replacement.…”
Section: Introductionmentioning
confidence: 99%